Congenital malformation and hemoglobin A1c in the first trimester among Japanese women with pregestational diabetes. Issue 12 (6th September 2021) - Nakanishi, Kentaro; Kanagawa, Takeshi; Fujikawa, Kei; Ishii, Keisuke; Waguri, Masako
Abstract: Aim: To investigate the incidence of major congenital malformations in Japanese women with pregestational diabetes, and to determine the cutoff value of hemoglobin A1c (HbA1c) in the first trimester associated with congenital malformations. Methods: This retrospective cohort study included singleton pregnancies in Japanese women with pregestational diabetes, including type 1 and type 2 diabetes, and specific types of diabetes due to other causes. The primary outcome was the incidence of major congenital malformations. The secondary outcome was the incidence of all congenital malformations. The cutoff value of HbA1c for congenital malformations was calculated using receiver operating characteristic curve analysis. The adjusted odds ratios (aOR) of major congenital malformations were calculated using multiple logistic regression analyses. Results: This study enrolled 292 patients, including 132 (45.2%) with type 1 diabetes, 156 (53.4%) with type 2 diabetes, and 4 (1.4%) with other specific types. The incidence rates of major congenital malformations and all congenital malformations were 7.2% (21/292) and 12.7% (37/292), respectively. The cutoff value of HbA1c in the first trimester for major malformations and for all congenital malformations was 6.5%. HbA1c ≥ 6.5% was significantly associated with major malformations (aOR 3.5; 95% confidence interval: 1.2–12.6; p  = 0.018). Conclusion: The incidence of major congenital malformations significantly increased in pregnant Japanese women with HbA1c values of 6.5% or higher. The recommended HbA1c value during the first trimester used in other countries can be applied to pregnant Japanese women.